Release of potassium from rock powder by the yeast Torulaspora globosa - Rosa-Magri, Márcia Maria; Avansini, Simoni Helena; Lopes-Assad, Maria Leonor; Tauk-Tornisielo, Sâmia Maria [UNESP]; Ceccato-Antonini, Sandra Regina (Brazilian Archives of Biology and Technology, 2012)
The alteration of minerals in rocks and the availability of elements for plant nutrition require long periods of time, and microorganisms are thought to induce the release of potassium and phosphate from rocks. In this context, this work evaluates the role of the yeast Torulaspora globosa, isolated from the sugar cane rhizosphere, in the solubilization of potassium from alkaline ultramafic rock powder. The experiments were performed in liquid medium, with or without agitation, at 30°C with the following treatments: culture medium + alkaline ultramafic; culture medium + yeast suspension; and culture medium + yeast suspension + alkaline ultramafic. The results showed that as much as 38% of the total potassium in the rock was released in the medium with the yeast during a 15-day period of incubation. Acid production may be the mechanism by which the yeast solubilizes potassium because the total acidity increased during the sampling period. Agitation (which increased oxygen availability) resulted in approximately 20% more biosolubilization of the alkaline ultramafic rock than with the static culture. These data indicate the potential for this yeast in biosolubilization processes and biofertilizer production.
Keywords: biosolubilization; insoluble rocks; alkaline ultramafic